Gonioscopy-Assisted Transluminal Trabeculotomy following Failed Glaucoma Surgery in Primary Congenital Glaucoma: One-Year Results - Abdelrahman M. Elhusseiny; Reem M. Aboulhassan; Yasmine M. El Sayed; Ghada I. Gawdat; Hala M. Elhilali (Case Reports in Ophthalmological Medicine)
Purpose. To evaluate the one-year outcomes of gonioscopy-assisted transluminal trabeculotomy (GATT) in primary congenital glaucoma (PCG) with a history of prior glaucoma surgery. Methods. A retrospective chart review was performed to identify all PCG patients≤16 years who underwent GATT surgery at Cairo University Children’s Hospital from January 2016 to March 2022. Pre- and postoperative intraocular pressure (IOP) and glaucoma medications were collected at 1, 3, 6, 9, 12, and last follow-up visits. Success was defined as IOP≤21 mmHg without (complete) or with (qualified) glaucoma medications at the last follow-up. Results. Seven eyes of 6 subjects were included in the study. The mean IOP was statistically significantly reduced from 25.7±5.9 mmHg preoperatively to a mean IOP of 12±1.5 mmHg (P=0.001) at 12 months and 11.5±1.2 mmHg (P=0.001) at the last follow-up visit. Six eyes (85.7%) achieved complete success, and one eye (14.2%) achieved qualified success. No patients required further glaucoma procedures. No serious intra- or postoperative complications were identified. Conclusions. Our early experience highlights that GATT can be performed as an alternative procedure before considering conjunctival or scleral glaucoma surgeries.